Binder for lithium ion battery, aqueous binder solution for lithium ion battery, electrode slurry for lithium ion battery, electrode for lithium ion battery, and lithium ion battery

CN123036686APending Publication Date: 2026-11-03LINTEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580024224.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-21
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

现有锂离子电池用水性浆料在与高pH活性物质一起制造时容易导致电极破裂,并且固体成分的分散稳定性差,影响涂敷性。

Method used

A water-soluble polymer with a specific composition is used as a binder, containing 5-80 mol% of hydroxyl-containing vinyl ether structural units and 13 wt% of an aqueous solution with a viscosity of 3000 mPa·s or higher at 23°C, combined with compound structural units containing (meth)acrylamide groups to form a stable aqueous dispersion of active substances.

Benefits of technology

Even when used with high-pH active materials, it can form a stable electrode, improve the dispersion stability of solid components, prevent electrode breakage, and enhance coating properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

A binder for a lithium ion battery, which contains a water-soluble polymer (A) containing 5 to 80 mol% of a structural unit derived from a hydroxyl group-containing vinyl ether (a) in all structural units of the water-soluble polymer (A), and a viscosity of a 13 mass% aqueous solution of the water-soluble polymer (A) is 3,000 mPa·s or more at 23°C as measured with a B-type viscometer, the binder for a lithium ion battery being used for forming an electrode of an active material having a pH of 10 or more, which contains an active material aqueous dispersion liquid measured by a given method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesives for lithium-ion batteries, aqueous solutions of adhesives for lithium-ion batteries, electrode slurries for lithium-ion batteries, electrodes for lithium-ion batteries, and lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries are already used in electronic devices such as mobile phones and laptops. In recent years, their application in automotive and household power storage batteries has also been developing.

[0003] Lithium-ion batteries consist of components such as a positive electrode, a negative electrode, a separator, and an electrolyte. The positive and negative electrodes are manufactured by coating an electrode slurry onto a current collector and then drying it. The electrode slurry is a mixture of active materials, conductive additives, binders, solvents, etc., that enable the insertion and extraction of lithium ions.

[0004] Polyvinylidene fluoride (PVDF) and other similar materials are widely used as binders in electrode formation. However, PVDF requires dissolution in organic solvents such as N-methylpyrrolidone, and organic solvents are also used as the liquid medium in electrode slurries. In recent years, however, from the perspective of environmental impact and cost, the requirements for processes using electrode slurries employing water as the liquid medium (hereinafter referred to as "aqueous slurries") have been continuously increasing. Therefore, the development of water-soluble binders applicable to aqueous slurries has been undertaken.

[0005] Patent Document 1 describes an electrode adhesive comprising a polymer containing structural units derived from alkyl methacrylate monomers and structural units derived from ester monomers having specific aromatic groups.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2023-121816 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] However, with the expansion of applications for lithium-ion batteries in recent years, various active materials with functions corresponding to these applications have been developed and put into practical use. Among these active materials, there are those that exhibit a high pH when formulated into aqueous dispersions. According to the research of the inventors, if an active material exhibiting a high pH and an acrylic polymer are used to manufacture an aqueous slurry, electrode breakage will occur due to the deterioration of the acrylic polymer.

[0011] Furthermore, for adhesives used in water-based slurries, it is required to suppress the dispersion stability of solid components such as active substances in the slurry state, preventing sedimentation. Sedimentation of solid components in the slurry state can cause deviations in the thickness of the active substance layer formed by the slurry and deterioration in coatability, therefore it is desirable to suppress this.

[0012] The present invention was made in view of the above-mentioned actual situation, and its object is to provide a lithium-ion battery adhesive that can form an electrode even when manufactured with an active material exhibiting a high pH in an aqueous slurry, and has excellent dispersion stability of solid components in the slurry state; an aqueous solution of the lithium-ion battery adhesive using the lithium-ion battery adhesive; a lithium-ion battery electrode slurry; a lithium-ion battery electrode; and a lithium-ion battery.

[0013] Problem Solving Methods

[0014] The inventors conducted in-depth research and discovered that the above-mentioned problems could be solved by using a water-soluble polymer containing structural units from specific monomers in a given amount and having a specific viscosity, thus completing the present invention.

[0015] That is, the present invention relates to the following [1]~

[10] .

[0016] [1] An adhesive for lithium-ion batteries, comprising a water-soluble polymer (A),

[0017] The water-soluble polymer (A) contains 5-80 mol% of structural units derived from a hydroxyl-containing vinyl ether (a) in all its structural units.

[0018] A 13% by mass aqueous solution of the water-soluble polymer (A) has a viscosity of ≥3000 mPa·s, measured using a type B viscometer at 23°C.

[0019] The binder for lithium-ion batteries is used to form an electrode containing an active material with a pH of 10 or higher, which is an aqueous dispersion of the active material as determined by the following method.

[0020] <Method for pH determination of aqueous dispersions of active substances>

[0021] Add 10g of active substance to 90g of purified water, stir at 23℃ for 30 minutes, and then measure the pH of the supernatant of the aqueous dispersion of active substance after standing for 10 minutes at 23℃.

[0022] [2] According to the adhesive for lithium-ion batteries described in [1] above, wherein,

[0023] The water-soluble polymer (A) further contains structural units from the compound (b) containing (meth)acrylamide groups.

[0024] [3] The lithium-ion battery adhesive according to [1] or [2] above, wherein,

[0025] The hydroxyl-containing vinyl ether (a) has a hydroxyl value of 400 mg KOH / g or higher, as determined according to JIS K 0070:1992.

[0026] [4] The adhesive for lithium-ion batteries according to any one of [1] to [3] above, wherein,

[0027] The active material is lithium-doped SiO or a ternary cathode material.

[0028] [5] The adhesive for lithium-ion batteries according to any one of [1] to [4] above, wherein,

[0029] The viscosity change rate of the water-soluble polymer (A), as determined by the following method, is -15% to +100%.

[0030] <Methods for determining viscosity change rate>

[0031] Add 20g of purified water to 80g of a 13% by mass aqueous solution of the water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution A. Add 20g of a 10% by mass sodium hydroxide aqueous solution to 80g of a 13% by mass aqueous solution of the water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution B. Use viscosity test solutions A and B as the test objects, and measure the viscosity using an E-type viscometer at 23°C and 50 rpm. Set the viscosity of viscosity test solution A as V1 and the viscosity of viscosity test solution B as V2. Calculate the viscosity change rate based on V1 and V2 using the following formula (1).

[0032] Viscosity change rate (%) = (V2-V1)×100 / V1 (1).

[0033] [6] An aqueous solution of an adhesive for lithium-ion batteries, comprising:

[0034] The adhesive for lithium-ion batteries described in any one of [1] to [5] above, and water.

[0035] [7] According to the above [6], the aqueous solution of the adhesive for lithium-ion batteries, wherein,

[0036] The total content of the water-soluble polymer (A) and water in the total amount of the aqueous adhesive for lithium-ion batteries is 80-100% by mass.

[0037] [8] An electrode slurry for lithium-ion batteries, comprising:

[0038] The adhesive for lithium-ion batteries described in any one of [1] to [5] above,

[0039] The active substance, and water.

[0040] [9] An electrode for a lithium-ion battery, comprising:

[0041] The adhesive for lithium-ion batteries described in any one of [1] to [5] above, and

[0042] The active substance.

[0043]

[10] A lithium-ion battery having the lithium-ion battery electrode described above [9].

[0044] The effects of the invention

[0045] According to the present invention, a lithium-ion battery adhesive that can form an electrode even when manufactured with an active material exhibiting a high pH and has excellent dispersion stability of solid components in the slurry state, an aqueous solution of the lithium-ion battery adhesive using the lithium-ion battery adhesive, an electrode slurry for lithium-ion batteries, an electrode for lithium-ion batteries, and a lithium-ion battery can be provided. Detailed Implementation

[0046] In this specification, the lower limit and upper limit values ​​recorded in stages for the preferred numerical range can be combined independently. For example, based on the record "preferred to be 10 to 90, more preferably 30 to 60", the "preferred lower limit (10)" and the "more preferably upper limit (60)" can be combined to set "10 to 60".

[0047] In this specification, for example, "(meth)acrylic acid" means both "acrylic acid" and "methacrylic acid", and other similar terms are used in the same way.

[0048] In this specification, "structural unit" refers to a unit based on a single monomer structure formed by the polymerization of a single monomer molecule.

[0049] Adhesives for lithium-ion batteries

[0050] The lithium-ion battery adhesive of this embodiment (hereinafter also referred to as "the adhesive of this embodiment") contains a water-soluble polymer (A).

[0051] The aforementioned water-soluble polymer (A) contains 5 to 80 mol% of structural units derived from hydroxyl-containing vinyl ether (a) in all its structural units.

[0052] A 13% by mass aqueous solution of the above-mentioned water-soluble polymer (A) has a viscosity of over 3000 mPa·s, measured using a type B viscometer at 23°C.

[0053] The binder for lithium-ion batteries is used to form an electrode containing an active material with a pH of 10 or higher, which is an aqueous dispersion of the active material as determined by the following method.

[0054] <Method for pH determination of aqueous dispersions of active substances>

[0055] Add 10g of active substance to 90g of purified water, stir at 23℃ for 30 minutes, and then measure the pH of the supernatant of the aqueous dispersion of active substance after standing for 10 minutes at 23℃.

[0056] In the case of the adhesive of this embodiment, the water-soluble polymer (A) contains structural units from hydroxyl-containing vinyl ether (a) in the content within the given range described above. Thus, even when an aqueous slurry is manufactured together with an active substance that exhibits a pH of 10 or higher in the pH measurement method described above (hereinafter also simply referred to as "active substance exhibiting a pH of 10 or higher"), an electrode can be formed.

[0057] The exact reasons are unclear, but one possible reason is that the structural units of hydroxyl-containing vinyl ethers (a) have excellent resistance to hydrolysis in alkaline environments. Therefore, even when coexisting with the above-mentioned active substances that show a pH above 10 in water, the polymer is not easily hydrolyzed.

[0058] Furthermore, it can be inferred that by making the viscosity of a 13% by mass aqueous solution of the water-soluble polymer (A) at 23°C, measured using a type B viscometer (hereinafter also referred to as "the viscosity of the aqueous solution of the water-soluble polymer (A) at 23°C"), 3000 mPa·s or higher, the dispersion stability of the solid components in the slurry state is improved.

[0059] <Water-soluble polymer (A)>

[0060] The water-soluble polymer (A) contains structural units derived from a hydroxyl-containing vinyl ether (a).

[0061] It should be noted that, in this specification, "vinyl ether" refers to a compound having a vinyl group and an ether oxygen atom bonded to that vinyl group.

[0062] In addition, “water-soluble” in water-soluble polymer (A) means that it dissolves in more than 1 part by mass relative to 100 parts by mass of water at 23°C.

[0063] (Structural unit derived from hydroxyl-containing vinyl ether (a))

[0064] The structural unit from the hydroxyl-containing vinyl ether (a) is the structural unit formed by the addition reaction of the vinyl group present in the hydroxyl-containing vinyl ether (a).

[0065] The structural units derived from hydroxyl-containing vinyl ethers (a) contained in the water-soluble polymer (A) may be a single type or two or more types.

[0066] [Hydroxy-containing vinyl ethers (a)]

[0067] A hydroxyl-containing vinyl ether (a) is any compound having a hydroxyl group, a vinyl group, and an ether oxygen atom bonded to the vinyl group; there are no particular limitations.

[0068] The hydroxyl-containing vinyl ether (a) has one or more vinyl groups in one molecule, and from the viewpoint of suppressing gelation during synthesis, it is preferably three or less, more preferably two or less, and even more preferably one.

[0069] From the viewpoint of reactivity, flexibility, etc., the hydroxyl-containing vinyl ether (a) is preferably a vinyl ether having a hydroxyalkyl group having 1 to 3 carbon atoms, or a vinyl ether having a hydroxy polyoxyalkylene chain containing 2 or more oxyalkylene units having 1 to 3 carbon atoms.

[0070] Examples of vinyl ethers having 1 to 3 carbon atoms and containing 1 to 3 hydroxyalkyl groups include hydroxymethyl, 2-hydroxyethyl, and 3-hydroxypropyl.

[0071] Examples of vinyl ethers having a hydroxyalkyl group having 1 to 3 carbon atoms include hydroxymethyl vinyl ether, 2-hydroxyethyl vinyl ether, and 3-hydroxypropyl vinyl ether. Among these, 2-hydroxyethyl vinyl ether is preferred.

[0072] Examples of oxoalkylene units with 1 to 3 carbon atoms in hydroxyl-containing vinyl ethers (a) include oxomethylene units, oxoethylene units, and oxopropylene units.

[0073] The number of oxyalkylene units in the hydroxy polyoxyalkylene chain is two or more, preferably four or less, more preferably three or less, and even more preferably two.

[0074] Examples of hydroxyl-containing vinyl ethers (a) include diethylene glycol monovinyl ether, triethylene glycol monovinyl ether, dipropylene glycol monovinyl ether, and tripropylene glycol monovinyl ether. Among these, diethylene glycol monovinyl ether is preferred.

[0075] From the viewpoint of easily adjusting the viscosity of the water-soluble polymer (A) at 23°C to a preferred range, the hydroxyl value of the hydroxyl-containing vinyl ether (a), as determined according to JIS K 0070:1992, is preferably 400 mg KOH / g or more, more preferably 500 mg KOH / g or more, and even more preferably 600 mg KOH / g or more. The hydroxyl value of the hydroxyl-containing vinyl ether (a) can be 1500 mg KOH / g or less, or 1000 mg KOH / g or less.

[0076] [Content of structural units from hydroxyl-containing vinyl ethers (a)]

[0077] The content of structural units derived from hydroxyl-containing vinyl ethers (a) in the water-soluble polymer (A) is 5 to 80 mol in all structural units of the water-soluble polymer (A).

[0078] When the content of structural units from hydroxyl-containing vinyl ether (a) is 5 mol% or more, the polymer becomes soft and can suppress electrode breakage when used as an adhesive. Moreover, when the content of structural units from hydroxyl-containing vinyl ether (a) is 80 mol% or less, the generation of residual monomers during the synthesis of water-soluble polymer (A) can be suppressed.

[0079] From the same point of view as above, the content of the structural unit from the hydroxyl-containing vinyl ether (a) in the water-soluble polymer (A) is preferably 10 to 70 mol%, more preferably 20 to 60 mol%, and even more preferably 30 to 50 mol% of all the structural units of the water-soluble polymer (A).

[0080] (Structural unit from compound (b) containing (meth)acrylamide group)

[0081] The water-soluble polymer (A) preferably includes structural units from the compound (b) containing (meth)acrylamide groups, together with structural units from the hydroxyl-containing vinyl ether (a).

[0082] The structural unit of compound (b) containing a (meth)acrylamide group is formed by the addition reaction of the carbon-carbon double bond contained in the (meth)acryloyl group of compound (b).

[0083] The water-soluble polymer (A) contains structural units from compounds (b) containing (meth)acrylamide groups. The reactivity between monomers during the synthesis of the water-soluble polymer (A) is enhanced, and it tends to further suppress the generation of residual monomers.

[0084] It should be noted that in this specification, "(meth)acrylamide group" refers to the group represented by the following general formula (b-1).

[0085] [Chemical Formula 1]

[0086]

[0087] (where R is in the formula) b1 It represents a hydrogen atom or a methyl group. (Indicates the bonding site.)

[0088] The structural units derived from the compound (b) containing (meth)acrylamide groups contained in the water-soluble polymer (A) can be a single unit or two or more units.

[0089] [Compounds containing (meth)acrylamide groups (b)]

[0090] As for compound (b) containing a (meth)acrylamide group, any compound containing the above-mentioned (meth)acrylamide group is acceptable and there is no particular limitation. For example, compounds represented by the following general formula (b-2) can be cited.

[0091] [Chemical Formula 2]

[0092]

[0093] (where R is in the formula) b1 Represents a hydrogen atom or a methyl group. R b2 and R b3 Each of the following groups independently represents a hydrogen atom, or a hydrocarbon group with 1 to 20 substituted or unsubstituted carbon atoms, R b2 With R b3 (Optional bonding to form a ring.)

[0094] In the above general formula (b-2), R is used as... b2 and R b3 Examples of substituted or unsubstituted hydrocarbon groups with 1 to 20 carbon atoms include: alkyl groups with 1 to 20 carbon atoms, alkenyl groups with 2 to 20 carbon atoms, alkynyl groups with 2 to 20 carbon atoms, and aromatic hydrocarbon groups with 6 to 20 carbon atoms, etc. As R b2 With R b3 A ring formed by bonding can be exemplified by: R b2 and R b3 The bonded nitrogen atom forms a heterocycle with 2-20 carbon atoms, which is composed of R b2 and R b3 Heterocycles formed by bonded nitrogen atoms, one or more oxygen atoms, and 2 to 20 carbon atoms, etc.

[0095] The number of carbon atoms in a hydrocarbon group with 1 to 20 carbon atoms, whether substituted or unsubstituted, can be 1 to 10 or 1 to 5. It should be noted that this number of carbon atoms does not include the carbon atoms of the substituents.

[0096] Substituents that can be present in hydrocarbon groups with 1 to 20 carbon atoms, whether substituted or unsubstituted, include, for example, hydroxyl, halogen, cyano, nitro, carboxyl, amino, alkoxy, aryloxy, and acyloxy groups. The number of carbon atoms in the substituent can be 1 to 5 or 1 to 3.

[0097] Of the options above, from a reactivity point of view, R b2 and R b3 Hydrogen atoms are preferred.

[0098] Examples of compounds (b) containing a (meth)acrylamide group include: (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-tert-butyl (meth)acrylamide, N-hexyl (meth)acrylamide, and other N-alkyl (meth)acrylamides; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and other N,N-dialkyl (meth)acrylamides; N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, and other (meth)acrylamides with a hydroxyalkyl group; N-acryloylpyrrolidine, 3-acryloyl-2-oxazolidinone, 4-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and other (meth)acrylamides with a cyclic structure; etc. From a reactivity point of view, (meth)acrylamide is preferred.

[0099] [Content of structural units from compound (b) containing (meth)acrylamide groups]

[0100] In the case where the water-soluble polymer (A) of this embodiment contains structural units from the compound (b) containing (meth)acrylamide groups, the content of the structural units from the compound (b) containing (meth)acrylamide groups in the water-soluble polymer (A) is preferably 20 to 95 mol%, more preferably 30 to 90 mol%, even more preferably 40 to 80 mol%, and even more preferably 50 to 70 mol% of all structural units in the water-soluble polymer (A).

[0101] When the content of structural units from compound (b) containing (meth)acrylamide groups is at or above the lower limit mentioned above, there is a tendency to further suppress the generation of residual monomers during the synthesis of the water-soluble polymer (A). Furthermore, when the content of structural units from compound (b) containing (meth)acrylamide groups is below the upper limit mentioned above, there is a tendency to further suppress curling during electrode drying.

[0102] (Other structural units)

[0103] The water-soluble polymer (A) of this embodiment may further contain structural units (hereinafter also referred to as "other structural units") from monomers other than the hydroxyl-containing vinyl ether (a) and the compound (b) containing (meth)acrylamide groups, or may not contain them.

[0104] Other monomers mentioned above include, for example: α-olefin compounds such as ethylene, propylene, n-butene, and isobutene; (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate; unsaturated carboxylic acid compounds or their salts such as acrylic acid, methacrylic acid, and sodium acrylate; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; etc.

[0105] The other structural units contained in the water-soluble polymer (A) may be a single type or two or more types.

[0106] In the case where the water-soluble polymer (A) of this embodiment contains other structural units, the content of other structural units in the water-soluble polymer (A) is preferably 60 mol% or less, more preferably 40 mol% or less, and even more preferably 20 mol% or less.

[0107] (Total content of structural units from hydroxyl-containing vinyl ethers (a) and structural units from compounds containing (meth)acrylamide groups (b))

[0108] The total content of structural units from hydroxyl-containing vinyl ethers (a) and structural units from compounds (b) containing (meth)acrylamide groups in the water-soluble polymer (A) of this embodiment is preferably 40 to 100 mol% of all structural units in the water-soluble polymer (A), more preferably 60 to 100 mol%, and even more preferably 80 to 100 mol%.

[0109] (Viscosity of aqueous solution of water-soluble polymer (A) at 23°C)

[0110] As described above, the viscosity of a 13% by mass aqueous solution of the water-soluble polymer (A) measured at 23°C using a type B viscometer is above 3000 mPa·s.

[0111] In addition, the viscosity of a 13% by mass aqueous solution of the water-soluble polymer (A) at 23°C is preferably 4000 to 100000 mPa·s, more preferably 4500 to 50000 mPa·s, and even more preferably 5000 to 20000 mPa·s.

[0112] When the viscosity of the aqueous solution of water-soluble polymer (A) at 23°C is above the lower limit mentioned above, the dispersion stability of the solid components in the aqueous slurry state becomes better, and it tends to suppress binder migration and easily obtain better adhesion. In addition, when the viscosity of the aqueous solution of water-soluble polymer (A) at 23°C is below the upper limit mentioned above, it tends to improve the coatability of the slurry in the slurry state.

[0113] The viscosity of the aqueous solution of the water-soluble polymer (A) at 23°C can be determined by the method described in the examples.

[0114] <Viscosity change rate of aqueous solution of water-soluble polymer (A)>

[0115] The preferred water-soluble polymer (A) has a viscosity change rate of -15 to +100% as determined by the following method.

[0116] (Methods for determining the rate of change of viscosity)

[0117] Add 20g of purified water to 80g of a 13% by mass aqueous solution of the above-mentioned water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution A. Add 20g of a 10% by mass sodium hydroxide aqueous solution to 80g of a 13% by mass aqueous solution of the above-mentioned water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution B. Using the above-mentioned viscosity test solutions A and B as the test objects, the viscosity was measured using an E-type viscometer at 23℃ and 50rpm. The viscosity of the above-mentioned viscosity test solution A was set as V1, and the viscosity of the above-mentioned viscosity test solution B was set as V2. The viscosity change rate was calculated based on V1 and V2 using the following formula (1).

[0118] Viscosity change rate (%) = (V2 - V1) × 100 / V1 (1)

[0119] It should be noted that the more specific method for determining the viscosity change rate is as described in the examples.

[0120] When the viscosity change rate of the aqueous solution of water-soluble polymer (A) is within the above range, there is no decrease in battery performance due to polymer decomposition or cracking when the electrode is dried, and a stable electrode can be manufactured.

[0121] From the same point of view, the viscosity change rate of the aqueous solution of the water-soluble polymer (A) is preferably -15 to +90%, more preferably -10 to +80%, even more preferably -5 to +60%, and even more preferably 0 to +55%.

[0122] (Method for manufacturing water-soluble polymer (A))

[0123] The water-soluble polymer (A) can be manufactured by polymerizing raw material monomers, such as a hydroxyl-containing vinyl ether (a), a compound (b) containing a (meth)acrylamide group (as needed), and other monomers, in a solvent.

[0124] The polymerization method is not particularly limited, and can be any method such as solution polymerization or bulk polymerization. From a production point of view, solution polymerization is preferred, and solution polymerization using water as a solvent is more preferred.

[0125] A polymerization initiator is preferred when carrying out a polymerization reaction.

[0126] Examples of polymerization initiators include: azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropanediamine) dihydrochloride, and 2,2'-azobis(2-hydroxymethylpropanetronitrile); organic peroxides such as lauroyl peroxide, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl peroxybenzoate, and (3,5,5-trimethylhexanoyl) peroxide; and inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide. Among these, azo compounds are preferred, and 2,2'-azobis(2-methylpropanediamine) dihydrochloride is more preferred.

[0127] Polymerization initiators can be used alone or in combination of two or more.

[0128] The amount of polymerization initiator relative to the total amount of monomer (100 parts by mass) is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass.

[0129] The polymerization reaction is preferably carried out while heating is applied. The reaction temperature is, for example, 50~95℃, and the reaction time is, for example, 2~8 hours.

[0130] Monomers can be added all at once or gradually.

[0131] The polymerization reaction is preferably carried out under an inert atmosphere such as nitrogen while being stirred.

[0132] <Ingredients other than water-soluble polymer (A)>

[0133] The adhesive for lithium-ion batteries in this embodiment may or may not contain any components other than the water-soluble polymer (A).

[0134] As a component other than water-soluble polymer (A), examples of polymers other than water-soluble polymer (A) can be cited.

[0135] The content of the water-soluble polymer (A) in the binder for lithium ion batteries of the present embodiment is preferably 80 to 100 mass%, more preferably 90 to 100 mass%, and further preferably 95 to 100 mass%. The binder for lithium ion batteries of the present embodiment may be the water-soluble polymer (A) itself.

[0136] <Use of the binder for lithium ion batteries of the present embodiment>

[0137] The binder for lithium ion batteries of the present embodiment can be used to form an electrode containing the above-mentioned active substance exhibiting a pH of 10 or higher.

[0138] The electrode formed using the binder of the present embodiment may be a positive electrode or a negative electrode.

[0139] The active substance exhibiting a pH of 10 or higher is not particularly limited. As the negative electrode material, lithium-doped SiO is preferred, and as the positive electrode material, a ternary positive electrode material is preferred.

[0140] The average particle diameter (D 50 ) of lithium-doped SiO may be 0.01 to 30 μm, 0.1 to 20 μm, or 1 to 10 μm.

[0141] Examples of the ternary positive electrode material include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2 and other nickel-cobalt-manganese ternary positive electrode materials (NCM) represented by LiNi x Co y Mn z O2 (0<x<1, 0<y<1, 0<z<1, and x+y+z=1), LiNi 0.8 Co 0.15 Al 0.05 O2 and other nickel-cobalt-aluminum ternary positive electrode materials (NCA) represented by LiNi x Co y Al z O2 (0<x<1, 0<y<1, 0<z<1, and x+y+z=1), and the like.

[0142] The average particle size (D) of ternary cathode materials 50 The value can be 0.1~50μm, 0.5~30μm, or 1~15μm.

[0143] The shape of lithium-doped SiO or ternary cathode materials is not particularly limited; for example, they can be fragmented, spherical, flat, fibrous, etc.

[0144] The active material with a pH above 10 is not limited to lithium-doped SiO or ternary cathode materials. For example, it can be lithium pre-doped anode materials other than SiO, quaternary cathode materials, and other lithium composite oxides other than ternary cathode materials.

[0145] [Aqueous adhesive for lithium-ion batteries]

[0146] The aqueous solution of the adhesive for lithium-ion batteries in this embodiment (hereinafter also referred to as "the aqueous solution of the adhesive in this embodiment") is an aqueous solution of the adhesive for lithium-ion batteries containing the adhesive for lithium-ion batteries in this embodiment and water.

[0147] The electrode formed using the adhesive aqueous solution of this embodiment can be either a positive electrode or a negative electrode.

[0148] From a processability point of view, the content of water-soluble polymer (A) in the adhesive aqueous solution of this embodiment is preferably 1 to 40% by mass, more preferably 5 to 30% by mass, and even more preferably 10 to 20% by mass.

[0149] The adhesive aqueous solution of this embodiment may contain other components besides the adhesive and water of this embodiment (hereinafter also referred to as "other aqueous solution components"), or it may not contain any components.

[0150] Other components of an aqueous solution include, for example, solvents other than water, thickeners, wetting agents, pH adjusters, stabilizers, surfactants, antioxidants, and preservatives. Each of these other aqueous solution components can be used individually or in combination of two or more.

[0151] From the viewpoint of further fully demonstrating the effects of the present invention, the total content of water-soluble polymer (A) and water in the total amount of adhesive aqueous solution in this embodiment is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 95 to 100% by mass.

[0152] The method for manufacturing the adhesive aqueous solution in this embodiment is not particularly limited. For example, if water is used as a solvent when synthesizing the water-soluble polymer (A) and the water-soluble polymer (A) is obtained in the form of an aqueous solution, the aqueous solution of the water-soluble polymer (A) can be used directly as the adhesive aqueous solution in this embodiment.

[0153] Alternatively, if necessary, the water-soluble polymer (A) synthesized in the solvent can be dissolved in water at a desired time after separation. Other aqueous solution components can be added at any time.

[0154] Electrode slurry for lithium-ion batteries

[0155] The electrode slurry for lithium-ion batteries in this embodiment (hereinafter also referred to as "electrode slurry of this embodiment") is an electrode slurry for lithium-ion batteries containing the binder for lithium-ion batteries in this embodiment, the active material exhibiting a pH of 10 or higher, and water.

[0156] The electrode paste of this embodiment can be dried after being coated onto the current collector, thereby forming an active material layer on the current collector containing the active material and the binder of this embodiment.

[0157] The electrode formed using the electrode slurry of this embodiment can be either a positive electrode or a negative electrode.

[0158] In the electrode slurry of this embodiment, the content of the binder is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the active material, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass.

[0159] When the binder content in this embodiment is at or above the aforementioned lower limit, the strength of the active material layer can be further improved. Furthermore, when the binder content in this embodiment is below or above the aforementioned upper limit, it tends to suppress the increase in electrode resistance.

[0160] The electrode paste of this embodiment may contain conductive additives as needed.

[0161] Examples of conductive additives include: various types of graphite; carbon blacks such as acetylene black, Ketjen black, furnace black, and channel black; carbon fibers such as carbon nanofibers and carbon nanotubes; and metallic materials such as nickel, aluminum, and stainless steel.

[0162] The shape of the conductive additive is not particularly limited; it can be in the form of particles or fibers.

[0163] Conductive additives can be used alone or in combination of two or more.

[0164] When the electrode paste of this embodiment contains a conductive additive, the content of the conductive additive is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the active material, more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0165] From the viewpoint of coating properties, the concentration of solid components in the electrode slurry of this embodiment is preferably 20-90% by mass, more preferably 25-85% by mass, and even more preferably 30-80% by mass. It should be noted that, in this specification, the solid components of the electrode slurry refer to components other than the liquid medium.

[0166] The electrode slurry of this embodiment may contain the binder of this embodiment, the active substance exhibiting a pH of 10 or higher as described above, water, and components other than the conductive additive used as needed (hereinafter also referred to as "other slurry components"), or it may not contain any of these components. Examples of other slurry components include those identical to the other aqueous solution components described above.

[0167] The method for manufacturing the electrode paste in this embodiment is not particularly limited. For example, it can be manufactured by mixing the adhesive aqueous solution of this embodiment, the active substance exhibiting a pH of 10 or higher, the conductive additive used as needed, the additional solvent such as water, and other paste components by a known method.

[0168] As a mixing device, a mixing machine such as a ball mill, sand mill, planetary mixer, paint shaker, homogenizer, dispersion homogenizer, or homogenizer can be used.

[0169] Electrodes for lithium-ion batteries

[0170] The lithium-ion battery electrode of this embodiment (hereinafter also referred to as "the electrode of this embodiment") is a lithium-ion battery electrode containing the lithium-ion battery binder of this embodiment and the above-mentioned active material exhibiting a pH of 10 or higher.

[0171] The electrode in this embodiment can be either a positive electrode or a negative electrode.

[0172] The electrode of this embodiment preferably has an active material layer on the current collector containing the active material exhibiting a pH of 10 or higher and the binder of this embodiment.

[0173] In the electrode of this embodiment, the thickness of the active material layer is not particularly limited. For example, it can be 25~500μm, 50~300μm, or 100~200μm.

[0174] In the electrode of this embodiment, the content of the binder relative to 100 parts by mass of the active material is the same as the preferred range described in the description of the electrode slurry of this embodiment.

[0175] Furthermore, the electrode of this embodiment may contain the aforementioned conductive additive. In the electrode of this embodiment, the content of the conductive additive relative to 100 parts by mass of the active material is the same as the preferred range described in the description of the electrode slurry of this embodiment.

[0176] In addition, the electrode of this embodiment may contain the other slurry components and other aqueous solution components listed above.

[0177] The current collector is preferably formed of sheet-like metal.

[0178] Metals used as current collectors include, for example, iron, copper, aluminum, nickel, and stainless steel. Among these, aluminum foil is preferred as the current collector for the positive electrode, and copper foil is preferred as the current collector for the negative electrode.

[0179] The thickness of the current collector is, for example, 5~20μm.

[0180] The electrode of this embodiment can be manufactured by coating the electrode slurry of this embodiment onto the current collector and then drying it.

[0181] Examples of methods for coating the electrode paste of this embodiment onto the current collector include: reverse roller coating, scraper coating, direct roller coating, doctor blade coating, extrusion coating, curtain coating, gravure coating, rod coating, dip coating, and extrusion coating.

[0182] The electrode paste of this embodiment can be applied to only one side of the current collector or to both sides. When the electrode paste is applied to both sides of the current collector, it can be applied to each side separately or to both sides simultaneously. Furthermore, the electrode paste can be applied continuously to the entire surface of the current collector or applied intermittently. The amount and range of the electrode paste applied can be appropriately determined based on factors such as the size of the battery.

[0183] Methods for drying electrode paste coated on current collectors include, for example, methods using hot air, vacuum drying, and methods utilizing electromagnetic waves such as infrared, far-infrared, and near-infrared heaters.

[0184] The drying temperature of the electrode slurry is, for example, 80~150℃, and the drying time is, for example, 1~30 minutes.

[0185] The resulting electrodes can be shaped by cutting or other processes as needed.

[0186] [Lithium-ion battery]

[0187] The lithium-ion battery of this embodiment is a lithium-ion battery having the electrodes for a lithium-ion battery of this embodiment.

[0188] Examples of lithium-ion batteries in this embodiment include lithium-ion secondary batteries comprising a positive electrode, a negative electrode, an electrolyte, and a separator.

[0189] In the lithium-ion battery of this embodiment, at least one of the positive electrode and the negative electrode includes the electrode of this embodiment. Under this premise, it may include electrodes other than the electrode of this embodiment.

[0190] Electrodes, electrolytes, and separators other than those in this embodiment can be appropriately selected from known materials depending on the application.

[0191] The shape of the lithium-ion battery in this embodiment is not particularly limited, and it can be any shape such as coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.

[0192] Example

[0193] The present invention will be further described in detail below based on embodiments, but the present invention is not limited to these examples.

[0194] [Preparation of an aqueous solution of binder for lithium-ion batteries]

[0195] Manufacturing Example 1

[0196] 2013.60 g of purified water, 200.00 g of 2-hydroxyethyl vinyl ether, and 400.00 g of 50% (w / w) acrylamide aqueous solution were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The mixture was heated to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution consisting of 4.00 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 48.00 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Then, 442.09 g of purified water was added to obtain an aqueous solution of water-soluble polymer (A). This aqueous solution of water-soluble polymer (A) was used as an aqueous binder for lithium-ion batteries (the content of water-soluble polymer (A) was 13% (w / w).

[0197] Manufacturing Comparative Example 1

[0198] 2334.20 g of purified water, 147.35 g of 2-hydroxyethyl acrylate, 219.10 g of 50% (w / v) acrylamide aqueous solution, 91.70 g of acrylic acid, and 1.40 g of sodium methacrylate sulfonate were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The mixture was heated to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution consisting of 2.81 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 28.00 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Then, 133.23 g of 50% (w / v) sodium hydroxide aqueous solution was added for neutralization, yielding an aqueous solution of the water-soluble polymer. This aqueous solution of the water-soluble polymer was used as an aqueous binder for lithium-ion batteries (the content of the water-soluble polymer was 13% (w / v)).

[0199] Manufacturing Comparative Example 2

[0200] 1450 g of deionized water, 137.3 g of 2-hydroxyethyl vinyl ether, 188.6 g of 50% (w / w) acrylamide aqueous solution, and 0.09 g of sodium methacrylate sulfonate were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. After purging nitrogen to remove oxygen from the reaction system, the temperature was raised to 50°C. Then, 2.3 g of 2,2'-azobis(2-amidinylpropane) dihydrochloride and 50 g of deionized water were added, and the mixture was heated to 80°C for 3 hours to obtain an aqueous solution containing a water-soluble polymer (the content of the water-soluble polymer was 13% (w / w)).

[0201] Manufacturing Comparative Example 3

[0202] 665.26 g of purified water and 200.00 g of 2-hydroxyethyl vinyl ether were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The temperature was raised to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution containing 2.00 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 24.00 g of purified water was then added, and the reaction was carried out at 80°C for 4 hours. Finally, 662.58 g of purified water was added to the reaction solution. 1 The H-NMR analysis only confirmed the peak of the monomer, therefore it was determined that polymerization had not occurred.

[0203] Manufacturing Comparative Example 4

[0204] 1579.40 g of purified water, 15.00 g of 2-hydroxyethyl vinyl ether, 580.32 g of 50% (w / w) acrylamide aqueous solution, and 0.34 g of sodium methacrylate sulfonate were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The mixture was heated to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution of 3.05 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 36.66 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Then, 158.71 g of purified water was added to obtain an aqueous solution of the water-soluble polymer. This aqueous solution of the water-soluble polymer was used as an aqueous binder for lithium-ion batteries (the content of the water-soluble polymer was 13% (w / w)).

[0205] [Manufacturing of electrode slurry and electrodes for lithium-ion batteries]

[0206] Example 1

[0207] Add 12.1 g of the adhesive aqueous solution obtained in Manufacturing Example 1 and carbon black (manufactured by MTI Corporation, trade name "Super C65", specific surface area based on BET method: 62 m²) as a conductive additive to a glass container (capacity: 140 mL). 2 1.1 g (referred to as "CB" in Table 2) and 7.0 g of purified water were added and stirred at 2000 rpm for 30 minutes using a disperser (Primix, trade name "LABOLUTION", stirring part: Homo Disper 2.5). Then, ternary cathode material (lithium nickel cobalt manganese oxide, LiNi) was further added. 0.5 Co 0.2 Mn 0.3 O2, manufactured by JiangSu Easpring Material Technology Co., Ltd., trade name "ME5E12D", average particle size D 50 50.0 g of 12 μm (referred to as “NCM” ​​in Table 2) was used as the active material. After stirring at 2000 rpm for 10 minutes using the above-mentioned disperser, degassing was performed for 5 minutes at 0.04 atmosphere pressure, thereby obtaining an electrode slurry for lithium-ion batteries with a solid content concentration of 75.0% by mass.

[0208] The prepared lithium-ion battery electrode slurry was coated onto aluminum foil (manufactured by Hosen Co., Ltd., aluminum foil, 20 μm thick) using a coater with a gap of 205 μm. Then, it was dried in an oven at 120°C for 10 minutes to obtain a lithium-ion battery electrode (positive electrode) with an active material layer of 150 μm thickness on the current collector (aluminum foil).

[0209] Example 2

[0210] The active material was changed to lithium-doped SiO (manufactured by Baoquan Co., Ltd., trade name "LCL1485A-1", average particle size D). 50 The amount of purified water added was changed to 27.5 g, and the concentration of solid components in the slurry was changed to 58.0% by mass. Otherwise, the same electrode slurry for lithium-ion batteries was obtained as in Example 1.

[0211] The prepared lithium-ion battery electrode slurry was coated onto copper foil (manufactured by UACJ Corporation, rolled copper foil, 10 μm thick) using a coater with a 240 μm gap. Then, it was dried in an oven at 120°C for 10 minutes to obtain a lithium-ion battery electrode (negative electrode) with an active material layer of 150 μm thickness on the current collector (copper foil).

[0212] Comparative Examples 1, 4, and 6

[0213] By changing the type of adhesive aqueous solution to that shown in Table 2, an electrode (positive electrode) for lithium-ion batteries was obtained in the same manner as in Example 1.

[0214] Comparative Examples 2 and 5

[0215] By changing the type of adhesive aqueous solution to that shown in Table 2, an electrode (negative electrode) for lithium-ion batteries was obtained in the same manner as in Example 2.

[0216] Comparative Example 3

[0217] The type of adhesive aqueous solution was changed to that shown in Table 2, and the active material was changed to graphite (manufactured by Jiangxi Zichen Technology Co., Ltd., artificial graphite G1-C, average particle size D). 50 The amount of purified water added was changed to 42.0 g, and the concentration of solid components in the slurry was changed to 50.0% by mass. Otherwise, the same electrode slurry for lithium-ion batteries was obtained as in Example 1.

[0218] The prepared lithium-ion battery electrode slurry was coated onto copper foil (manufactured by UACJ Corporation, rolled copper foil, 10 μm thick) using a coater with a 280 μm gap. Then, it was dried in an oven at 120°C for 10 minutes to obtain a lithium-ion battery electrode (negative electrode) with an active material layer of 150 μm thickness on the current collector (copper foil).

[0219] [Evaluation of Electrode Formation Performance]

[0220] By visually inspecting the surface of the active material layer of the lithium-ion battery electrode made by the above method, the case where no cracks are generated in the active material layer is designated as "A", and the case where cracks are generated is designated as "F".

[0221] [Method for determining the concentration and rate of change of solid components in slurry after standing for 24 hours]

[0222] The lithium-ion battery electrode slurries obtained in each example were added to a glass container (capacity 20 mL) and left to stand for 24 hours with the lid on. After standing, approximately 1 g of the slurry was collected from the top and placed on an aluminum tray (weight W1), and weighed. The weight of the slurry placed on the aluminum tray at this point was designated as W2. The aluminum tray containing the slurry was dried in an oven at 120°C for 2 hours, and the weight W3 (weight of slurry + aluminum tray) after drying was measured. The solid content concentration of the slurry after standing for 24 hours was calculated using the following formula.

[0223] The concentration of solids in the slurry after standing for 24 hours (%) = (W3 - W1) × 100 / W2

[0224] Furthermore, the solid component concentration of the slurry after standing for 24 hours is compared with the solid component concentration of the slurry after feeding, and the change rate of solid component is calculated by the following formula.

[0225] Change rate of solids content (%) = [(Concentration of solids content in slurry after standing for 24 hours) - (Concentration of solids content in feed)] × 100 / Concentration of solids content in feed

[0226] [pH Determination Method for Active Substances]

[0227] 90g of purified water and 10g of active substance were added to a glass container (140mL capacity). An oval stir bar (diameter × total length: 10 × 20mm) was added, and the mixture was stirred for 30 minutes at 23℃ and 1000rpm using a magnetic stirrer to obtain an aqueous dispersion of the active substance. After stirring, the pH of the supernatant of the aqueous dispersion of the active substance was measured at 23℃ after standing for 10 minutes using a pH meter (HORIBA Advanced Techno, trade name "F-2000PI-S", electrode: Standard ToupH Electrode (9615S-10D)). The obtained pH was taken as the pH of the active substance.

[0228] [Method for determining the viscosity of aqueous solutions of water-soluble polymers at 23°C]

[0229] The viscosity of the aqueous solution (13% by mass of water-soluble polymer) of the adhesive for lithium-ion batteries obtained in each manufacturing example and comparative example was measured using a Type B viscometer (manufactured by BROOKFIELD, product name "Analog Viscometer RVT") at 23°C with the following measuring shaft at 50 rpm.

[0230] For viscosities above 500 mPa·s but below 1500 mPa·s: RV-3 measuring shaft

[0231] For viscosities above 1500 mPa·s but below 2000 mPa·s: RV-4 measuring shaft

[0232] For viscosities above 2000 mPa·s and below 5500 mPa·s: RV-5 measuring shaft

[0233] For viscosities above 5500 mPa·s and below 15000 mPa·s: RV-6 measuring shaft

[0234] For viscosities above 15000 mPa·s: RV-7 measuring shaft

[0235] [Method for determining the viscosity change rate of aqueous solutions of water-soluble polymers]

[0236] 20g of purified water was added to 80g of the aqueous solution of the lithium-ion battery adhesive (13% by mass aqueous solution of water-soluble polymer) obtained in each manufacturing example and comparative example. The mixture was stirred for 24 hours at 23°C and 20rpm using a mixing rotor to prepare viscosity measurement solution A. 20g of 10% by mass sodium hydroxide aqueous solution was added to 80g of the obtained aqueous solution of the adhesive (13% by mass aqueous solution of water-soluble polymer). The mixture was stirred for 24 hours at 23°C and 20rpm using a mixing rotor to prepare viscosity measurement solution B. Viscosity measurement solutions A and B were used as the measurement objects. The viscosity was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., trade name "RE-85U", conical rotor specification: 1°34'×R24) at 23°C and 50rpm. The viscosity of viscosity measurement solution A was set as V1, and the viscosity of viscosity measurement solution B was set as V2. The viscosity change rate was calculated using the following formula (1) based on V1 and V2.

[0237] Viscosity change rate (%) = (V2 - V1) × 100 / V1 (1)

[0238] The evaluation results of the water-soluble polymers obtained in each manufacturing example and manufacturing comparative example are shown in Table 1.

[0239]

[0240] The details of the monomers listed in Table 1 are as follows.

[0241] HEVE: 2-Hydroxyethyl vinyl ether

[0242] AM: Acrylamide

[0243] HEA: 2-Hydroxyethyl acrylate

[0244] AA: Acrylic acid

[0245] SMAS: Sodium methylpropenesulfonate

[0246] The evaluation results of the electrodes obtained in each embodiment and comparative example are shown in Table 2.

[0247]

[0248] As can be seen from Tables 1 and 2, the lithium-ion battery adhesive of this embodiment, which contains the water-soluble polymer (A) obtained in Manufacturing Example 1, has high alkali resistance and can form electrodes even when manufactured with an active material exhibiting a high pH in an aqueous slurry.

[0249] Furthermore, it is known that the lithium-ion battery binder of this embodiment, which contains the water-soluble polymer (A) obtained in manufacturing Example 1, exhibits excellent dispersion stability of its solid components in the slurry state.

Claims

1. An adhesive for lithium-ion batteries, comprising a water-soluble polymer (A), The water-soluble polymer (A) contains 5-80 mol% of structural units derived from a hydroxyl-containing vinyl ether (a) in all its structural units. A 13% by mass aqueous solution of the water-soluble polymer (A) has a viscosity of ≥3000 mPa·s, measured using a type B viscometer at 23°C. The binder for lithium-ion batteries is used to form an electrode containing an active material with a pH of 10 or higher, which is an aqueous dispersion of the active material as determined by the following method. <Method for pH determination of aqueous dispersions of active substances> Add 10g of active substance to 90g of purified water, stir at 23℃ for 30 minutes, and then measure the pH of the supernatant of the aqueous dispersion of active substance after standing for 10 minutes at 23℃.

2. The adhesive for lithium-ion batteries according to claim 1, wherein, The water-soluble polymer (A) further contains structural units from the compound (b) containing (meth)acrylamide groups.

3. The adhesive for lithium-ion batteries according to claim 1 or 2, wherein, The hydroxyl-containing vinyl ether (a) has a hydroxyl value of 400 mg KOH / g or higher, as determined according to JIS K 0070:1992.

4. The adhesive for lithium-ion batteries according to claim 1 or 2, wherein, The active material is lithium-doped SiO or a ternary cathode material.

5. The adhesive for lithium-ion batteries according to claim 1 or 2, wherein, The viscosity change rate of the water-soluble polymer (A), as determined by the following method, is -15% to +100%. <Methods for determining viscosity change rate> Add 20g of purified water to 80g of a 13% by mass aqueous solution of the water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution A. Add 20g of a 10% by mass sodium hydroxide aqueous solution to 80g of a 13% by mass aqueous solution of the water-soluble polymer (A), stir for 24 hours to prepare viscosity test solution B. Use viscosity test solutions A and B as the test objects, and measure the viscosity using an E-type viscometer at 23°C and 50 rpm. Set the viscosity of viscosity test solution A as V1 and the viscosity of viscosity test solution B as V2. Calculate the viscosity change rate based on V1 and V2 using the following formula (1). Viscosity change rate (%) = (V2-V1)×100 / V1 (1).

6. An aqueous solution of an adhesive for lithium-ion batteries, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2, and water.

7. The aqueous adhesive solution for lithium-ion batteries according to claim 6, wherein, The total content of the water-soluble polymer (A) and water in the total amount of the aqueous adhesive for lithium-ion batteries is 80-100% by mass.

8. An electrode slurry for lithium-ion batteries, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2 The active substance, and water.

9. An electrode for a lithium-ion battery, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2, and The active substance.

10. A lithium-ion battery having the electrode for a lithium-ion battery as described in claim 9.

Citation Information

Patent Citations

  • Binder for electrodes, electrodes, and energy storage device

    JP2023121816A